COOPERAÇÃO INTERMUNICIPAL COMO ESTRATÉGIA DE DESENVOLVIMENTO: o caso do consórcio intermunicipal de produção e abastecimento de São Luís/MA 1997/2010 - PIRES, Selma Sousa (2014)
This work aims to comprehend the strategy of production and supply vindicated by Intermunicipal Consortium of Production and Supply, known as Consórcio Intermunicipal de Produção e Abastecimento (CINPRA), and its major impacts over production of the consortiated municipalities. Due the increase of the municipalities duties with regard to decentralized social policies, many municipalities have articulated, forming public consortia, with the aim of expanding its management s capacity and availability of resources for the optimization of rendered services. This kind of institutional arrangement allows a new agreement practice and intergovernmental cooperation, since a single action would have a very high cost to municipality, on account of it the need to add partnerships with the same goal, allowing the institutionalization of cooperative and integrative aspects, by making easy the decentralization of politics, lowering the cost, in order to regard local demands. In Maranhão s case, the experience of consortium dates back to 1997, when it was founded in São Luís, the Consórcio Intermunicipal de Produção e Abastecimento. It was verified that the strategy adopted by consortium, of production and supply, was a conservative strategy of productivist bias, which imagines production and supply just as production, storage, distribution and trading. And besides all embarrassments CINPRA s got through, that experience brought a learning experience for cooperation in Maranhão, because it shows that municipalities together can access a range of information and a set of cultural practices which small towns, just by themselves, would have many difficulties to access and shows that it is possible to support the development from the bottom up, having the region as a planning unit and execution of actions.